Infrapatellar Fat Pad Stem Cells Responsiveness to Microenvironment in Osteoarthritis: From Morphology to Function - Stocco, Elena; Barbon, Silvia; Piccione, Monica; Belluzzi, Elisa; Petrelli, Lucia; Pozzuoli, Assunta; Ramonda, Roberta; Rossato, Marco; Favero, Marta; Ruggieri, Pietro; Porzionato, Andrea; Di Liddo, Rosa; et al. (Frontiers in Cell and Developmental Biology, 2019)
Recently, infrapatellar fat pad (IFP) has been considered as a source of stem cells for cartilage regeneration in osteoarthritis (OA) due to their ability for differentiation into chondrocytes. However, stressful conditions, like that related to OA, may induce a pathogenic reprogramming. The aim of this study was to characterize the structural and functional properties of a new population of stem cells isolated from osteoarthritic infrapatellar fat pad (OA-IFP). Nine OA patients undergoing total knee arthroplasty were enrolled in this study (median age = 74 years, interquartile range [IQR] = 78.25-67.7; median body mass index = 29.4 Kg/m², IQR = 31.7-27.4). OA-IFP stem cells were isolated and characterized for morphology, stemness, metabolic profile and multi-differentiative potential by transmission electron microscopy, flow cytometric analysis, gene expression study and cytochemistry. OA-IFP stem cells displayed a spindle-like morphology, self-renewal potential and responsiveness (CD44, CD105, VEGFR2, FGFR2, IL1R, IL6R) to microenvironmental stimuli. Characterized by high grade of stemness (STAT3, NOTCH1, c-Myc, OCT-4, KLF4 and NANOG), the cells showed peculiar immunophenotypic properties (CD73+/CD39+/CD90+/CD105+/CD44-/+/CD45-). The expression of HLA-DR, CD34, Fas and FasL was indicative of a possible phenotypic reprogramming induced by inflammation. Moreover, the response to mechanical stimuli together with high expression level of COL1A1 gene, suggested their possible protective response against in vivo mechanical overloading. Conversely, the low expression of CD38/NADase was indicative of their inability to counteract NAD+-mediated OA inflammation. Based on the ultrastructural, immunophenotypic and functional characterization, OA-IFP stem cells were hypothesized to be primed by the pathological environment and to exert incomplete protective activity from OA inflammation. Keywords: Infrapatellar Fat Pad, osteoarthritis, stem cells, inflammation, reprogramming